L'effet des corridors de coupe sur les modalités de regénération forestière dans l'érablière à hêtre. - Valiquette, Jean-Pierre. (University of Ottawa (Canada), 1993)
Strip cutting, from its form and dimension, may be called a landscape element; it is also a disturbance which brings about sudden changes in the resources of the natural environment, particularly in forest vegetation. Therefore, the purpose of this thesis is to determine the spatial variation (in vertical stratification and horizontal structure) of deciduous forest vegetation in three strip corridors of variable widths (30, 60 and 90 metres). To this effect, quantitative measures of composition and specific diversity have been taken, as well as other measures of variables closely related to vegetation. The use of factorial methods (correspondence analysis, grouping method) completes the information gathered on vegetation dynamism in strip corridors. The results of this study indicate that the width of the corridor has, to a certain extent, a structuring effect on composition and specific diversity, and has an influence on the succession pattern. All three strip corridors are sufficiently regenerated, and the 30 metre corridor shows the highest specific diversity. The subject is dealt with in terms of both forest regeneration conditions and landscape ecology, since the effect of corridor width on secondary vegetation dynamism is studied.
Keywords: Geography.